Building the Implementation of Digital Learning through Supportive Leadership of Principals and Professional Competencies of Teachers: The Role of Mediation of Self-Efficacy of Public Elementary School Teachers - Nila Prianti; Merika Setiawati; Nellitawati; Ahmad Sabandi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Digital transformation in elementary education requires more than technological infrastructure; it also depends on leadership support, teacher competence, and teachers’ confidence in using technology. This study examined the effects of supportive principal leadership and teacher professional competence on digital learning implementation, with teacher self-efficacy as a mediating variable in public elementary schools in Kecamatan Pulau Punjung, Kabupaten Dharmasraya. A quantitative explanatory design was employed involving 186 teachers selected from a population of 336 teachers through proportional random sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess the measurement model, structural relationships, and mediation effects. The findings indicate that supportive principal leadership and teacher professional competence positively contribute to digital learning implementation. Teacher self-efficacy also plays an important role in strengthening teachers’ implementation of digital learning. Furthermore, the mediation analysis indicates that teacher self-efficacy functions as an intervening mechanism through which supportive leadership and professional competence contribute to digital learning implementation. These findings suggest that successful digital learning in elementary schools cannot be achieved through technology provision alone. Schools need to combine supportive leadership, continuous development of teacher professional competence, and efforts to strengthen teachers’ confidence in using digital technology. The study provides practical implications for principals and education authorities in designing integrated strategies for sustainable digital learning implementation.